Measuring the Datum or Pugh method's efficiency for selecting biomedical technology (2009)
Objective Determining the Pugh multicriteria method's effectiveness as a selection tool when acquiring new technology. Materials and Methods The state of the art regarding multicriteria method use was studied; the Datum or Pugh method was selected. The size of the sample of experts participating in the trial was calculated and characterised; a data sample of 23 experts was thus obtained. Electrocardiography technology was selected by using the selected decision-making method; 5 models from different providers were used. Results 46 tests were conducted. The model labelled '3' was selected as referent in most cases, whilst the model labelled '5' was selected as being the best option in most cases. Conclusions The Pugh method was effective as a method for decision-making when selecting biomedical technologies as the same model was always selected by the experts as being the best option in 87% of the tests applied.